2017
DOI: 10.1016/j.pec.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Communication behaviors and patient autonomy in hospital care: A qualitative study

Abstract: A B S T R A C TBackground: Little is known about how hospitalized patients share decisions with physicians. Methods: We conducted an observational study of patient-doctor communication on an inpatient medicine service among 18 hospitalized patients and 9 physicians. A research assistant (RA) approached newly hospitalized patients and their physicians before morning rounds and obtained consent. The RA audio recorded morning rounds, and then separately interviewed both patient and physician. Coding was done usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 17 publications
2
32
0
5
Order By: Relevance
“…The anticipated benefits of accessing information from the PA about their personal care and treatment were attractive to several participants. These responses are congruent with findings from the literature indicating that patients receive insufficient personal information from their doctors during hospital ward rounds 46 . The psychological benefits of patient information in the hospital context are also recognized in terms of helping patients know what to expect, thereby reducing uncertainty and anxiety 20,21 …”
Section: Discussionsupporting
confidence: 83%
“…The anticipated benefits of accessing information from the PA about their personal care and treatment were attractive to several participants. These responses are congruent with findings from the literature indicating that patients receive insufficient personal information from their doctors during hospital ward rounds 46 . The psychological benefits of patient information in the hospital context are also recognized in terms of helping patients know what to expect, thereby reducing uncertainty and anxiety 20,21 …”
Section: Discussionsupporting
confidence: 83%
“…Patient-centred information provision is recognised as complex because needs and preferences frequently vary dependent on personal characteristics and context [50]. Acute hospital encounters pose a particular challenge given the limited time generally available for processing information [51]. Yet despite most participants in this study experiencing a single hospital encounter, they reported PAs having successfully linked information provision about care management to participant need.…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision making is also arguably more effective as a collaborative process over time than a one-off decision [52]. Additionally, patient preferences for involvement in decision-making can differ widely especially in the hospital setting [51, 53], which is likely to influence how clinicians interpret these preferences. In this study, most participants expressed appreciation with the PA for enabling a better understanding of their health condition and treatment, even without evidence of shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…General Medical Council and Department of Health consent guidelines suggest that clinicians respect the specific views, beliefs and preferences of the patient and make no assumptions about which outcomes are most important to them [10,11]. ‘Adequately’ informed consent is difficult to measure, due to clinicians over‐estimating patient understanding and under‐estimating difficulties with information recall [12]. Patients and clinicians often struggle to agree on the concept of risk.…”
Section: Introductionmentioning
confidence: 99%